The Effect of -Chitosan from Litopenaeus vannamei on Fibroblast in the Oral Mucosal Wound Healing Process - Fakhrurrazi, Fakhrurrazi; Hakim, Rachmi Fanani; Rachman, salwa salsabila (Cakradonya Dental Journal, 2025)
The wound healing process consists of four main phases: hemostasis, inflammation, proliferation, and remodeling. The proliferative stage in wound healing is characterized by the formation of new tissue and the presence of fibroblast cells that migrate to the wound area to close it. Vaname shrimp (Litopenaeus vannamei) chitosan is known as a material that is non-toxic and has biocompatibility, biodegradation ability, polyelectrolyte properties, and has been shown to have antimicrobial and accelerated wound healing. The purpose of this study was to observe the effect of Vaname shrimp chitosan gel on wound healing by examining the histological changes on the 14th day. This study was a laboratory experimental study on rats. Fifteen rats were divided into three groups: K+, K-, and KP. Wound surface areas were applied with chitosan from Vaname, commercial chitosan gel, and distilled water gel. Vaname shrimp chitosan gel was applied topically on wound surfaces in the treatment group twice a day and in the control group with distilled water gel. Fourteen days after treatment, all wounds were observed for their healing progress histologically, and Hematoxylin-Eosin staining was used. The results showed that the number of fibroblast cells in the Vaname shrimp chitosan group showed a significant difference between the control group, which had an average of 100.3, the negative control had an average of 110.2, and the Vaname group had an average of 90.2. The study can be concluded that there is an effect of -Kitosan from Vaname shrimp on wound healing (p=0.000).